Preparation and characterization of 45S5 bioactive glass‐based scaffolds loaded with PHBV microspheres with daidzein release function. Issue 6 (3rd April 2017) - Macías‐Andrés, Víctor I.; Li, Wei; Aguilar‐Reyes, Ena A.; Ding, Yaping; Roether, Judith A.; Harhaus, Leila; León‐Patiño, Carlos A.; Boccaccini, Aldo R.
Abstract: Poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) microsphere loaded 45S5 bioactive glass (BG) based scaffolds with drug releasing capability have been developed. PHBV microspheres with a mean particle size 4 ± 2 μm loaded with daidzein were obtained by oil‐in‐water single emulsion solvent evaporation method and applied to the surface of BG scaffolds by dip coating technique. The morphology, in vitro bioactivity in simulated body fluid (SBF), mechanical properties and drug release kinetics of microsphere loaded scaffolds were studied. The microspheres were shown to be homogeneously dispersed on the scaffold surfaces. It was confirmed that hydroxyapatite crystals homogeneously grew not only on the surface of the scaffold but also on the surface of the microspheres within 3 days of immersion in SBF. The daidzein release from the microsphere loaded scaffolds lasted almost 1 month and was determined to be diffusion controlled. The microsphere loaded BG scaffolds with daidzein releasing capability obtained in this study are a candidate for bone tissue engineering. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1765–1774, 2017.